2015
DOI: 10.1016/j.brainresbull.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Past, present and future of spike sorting techniques

Abstract: Spike sorting is a crucial step to extract information from extracellular recordings. With new recording opportunities provided by the development of new electrodes that allow monitoring hundreds of neurons simultaneously, the scenario for the new generation of algorithms is both exciting and challenging. However, this will require a new approach to the problem and the development of a common reference framework to quickly assess the performance of new algorithms. In this work, we review the basic concepts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
374
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 388 publications
(380 citation statements)
references
References 82 publications
6
374
0
Order By: Relevance
“…2B). Recording the spikes of the same neuron on multiple, closely located electrodes significantly enhances the quality of spike sorting and increases the single-unit yield (Gray et al 1995;Harris et al 2000;Quiroga 2012;Rey et al 2015). On the other hand, with a different configuration, where the recording sites are selected apart from each other with equal spacing (Fig.…”
Section: Electrophysiological Recording Capabilities Of the Edc Systemmentioning
confidence: 99%
“…2B). Recording the spikes of the same neuron on multiple, closely located electrodes significantly enhances the quality of spike sorting and increases the single-unit yield (Gray et al 1995;Harris et al 2000;Quiroga 2012;Rey et al 2015). On the other hand, with a different configuration, where the recording sites are selected apart from each other with equal spacing (Fig.…”
Section: Electrophysiological Recording Capabilities Of the Edc Systemmentioning
confidence: 99%
“…Neural signal decoding is a critical signal processing stage required by CNS-and PNS-based neuroprostheses, mainly based on spike sorting algorithms to analyse the single neuron activity from extra-cellular recordings [5]. Thanks to the evolution of the neuronal interface at the PNS level with intrafascicular electrodes characterized by a good selectivity [6], in principle it is possible to perform decoding on the PNS with techniques similar to those exploited for the CNS.…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…Multi-unit activity represents the pooled spiking activity of many neurons recorded on a single electrode. It can be generated simply by thresholding extracellular voltage signals, and thus avoids computationally costly spike sorting algorithms [40]. It has been shown that in the motor cortex multi-unit activity of a single channel may carry a similar amount of information about a movement as the single units extracted from the same recording channel [3], [41].…”
Section: Discussionmentioning
confidence: 99%